Post-buckling analysis of a fiber reinforced composite beam with crack - Akbaş, Şeref Doğuşcan (Pergamon-Elsevier Science Ltd, 2019)
In this paper, the post-buckling analysis of a cracked fiber reinforced composite (FRC) beam is investigated under a compressive load. In the solution of the problem, the finite element method is used within the first shear beam theory. The total Lagrangian approach is used in the nonlinear kinematic relations. The crack is modelled as a rotational spring. In the nonlinear solution of the post-buckling problem, the Newton-Raphson method is used. The effects of the fibre orientation angles, the volume fraction of the fibre, the crack depth and the crack locations on the post-bucking responses of the FRC beams are investigated in numerical results. The results show that the crack depth, the fibre orientation angles and the volume fraction of fibre have important role in the post-buckling responses of the FRC beams.
Keywords: Fiber reinforced composite; Post-buckling analysis; Beams; Crack; Total Lagrangian